Analısıs kualıtatıf senyawa rhodamın B pada saus jajanan “tusuk-tusuk” dı taman Berkampung kota Tarakan menggunakan metode rapid test kit - Faizal Mustamin; Irma Novrianti; Muhammad Aris; Asma Asma (Politeknik Kaltara, 2022)
Food is a basic need for living things. Some foods are available in the form of snacks and usually contain additional ingredients such as coloring. Often manufacturers misuse the use of dyes for textiles such as rhodamine B and leather used to color food ingredients. This study aims to determine the content of rhodamine B in the